Integration of eMental health technologies into traditional community-based interventions. (30th September 2020) - Turmaine, K; Picot Ngo, C; Le Jeannic, A; Roelandt, J L; Chevreul, K; Dumas, A
Abstract: Background: Very little research has been conducted to appraise the merits of including municipalities and their local health providers in the promotion of digital health programmes. While more and more municipalities have locally implemented a health strategic plan and have focused on building local network of professionals, how do the latter react to the implementation of innovative e-mental health community-based programmes? Methods: In 2018, 42 French municipalities volunteered to promote StopBlues, a digital health tool aimed at preventing mental distress and suicide. In each municipality, a local delegate was responsible for the promotion of the tool. Using observations, questionnaires and interviews with the delegates, we analysed how the promotion of StopBlues® was conducted in each setting. 2/3 of these municipalities started the promotion directly, and in 2019, a second wave of municipalities launched the promotion with a stronger support from the research team backed by the French World Health Organization Collaborating Centre for Research and Training in Mental Health (WHOCC). Results: The use of digital technology in the implementation of a mental health programme received a mixed reception from the local health professionals because of its innovative aspect. 2/3 of the delegates declared that they were struggling to create a stronger network of local partners including private medical practioners. 63% of the respondents stated that their municipalities got involved in the programme for networking purposes. Conclusions: Digital technologies have initiated a paradigm shift in the way community-based health programmes are set up but need to strengthen their territorial anchorage in order to be accepted and used at the local level. Key messages: Digital technology can be a strong lever against health inequities but its effectiveness has to be studied carefully. Digital technolgy has to be implemented in local settings with the collaboration of local actors in order to be accepted and used.